AN INTEGRATED MODEL FOR CLASSIFYING PROJECTS AND PROJECT MANAGERS AND PROJECT ALLOCATION - Oliveira, Elaine C B de; Alencar, Luciana Hazin; Costa, Ana Paula Cabral Seixas (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
This paper puts forward an integrated model to support the process of classifying projects and project managers (PM) using a multiple criteria decision aid (MCDA) approach and allocating projects according to organizational restrictions through mathematical programming. The model was formulated after reviewing the literature and being guided by the findings of searches; we used a MCDA method for project and PM classification (first stage) and mathematical programming for project allocation (second stage). A practical application of the proposed model was implemented at a Brazilian electric energy company. The results demonstrated that it was possible to classify projects and project managers into definable categories, thereby enabling the process of project allocation to be undertaken more effectively. The project allocation process can be conducted in a systematic and more efficient way. The proposed model can support an organization by allocating its most critical projects to its best qualified and experienced professionals.